The study of the phenomena of «hope» and «hopelessness» in psychology - S. N. Savinkov (Вестник университета)
The phenomena hope and hopelessness as actual problems of modern psychology, which are an integral part of the process of studying the subjective self-assessment of the individual, - have been considered. The data in the works of leading foreign and domestic psychologists, covering this problem, have been shown. The results of a study conducted among adolescents and reflecting the level of hope/hopelessness in this age period have been adduced. The ambiguous (ambivalent) nature of the phenomena of hope and hopelessness, which they carry in the life of the individual, as well as their relationship with emotional states and mental processes, - have been noted.